ATEX-Explosive Atmospheres Risk Assessment, Control and Compliance - Jespen, Torben (Springer Series in Reliability Engineering,, 2016)
This book details how safety (i.e. the absence of unacceptable risks) is ensured in areas where potentially explosive atmospheres (ATEX) can arise. The book also offers readers essential information on how to comply with the newest (April 2016) EU legislation when the presence of ATEX cannot be avoided. By presenting general guidance on issues arising out of the EU ATEX legislation - especially on zone classification, explosion risk assessment, equipment categorization, Ex-marking and related technical/chemical aspects - the book provides equipment manufacturers, responsible employers, and others with the essential knowledge they need to be able to understand the different - and often complicated - aspects of ATEX and to implement the necessary safety precautions. As such, it represents a valuable resource for all those concerned with maintaining high levels of safety in ATEX environments.